Kilka uwag o celach, metodach i kompetencji Unii Europejskiej do ujednolicania prawa prywatnego dotyczącego przepływu towarów - Machnikowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper concerns objectives, methods and competences of the European Union to pursue the harmonization of Member States’ private laws governing the movement of goods. The author presents legal basis for the harmonization of private law in EU primary law. He discusses the limitations of a method primarily used — harmonization by means of directives. In the author’s view, economic arguments used in favour of harmonization are not entirely convincing and until now the European Commission has not achieved the right balance between the three basic values that come into play: proper functioning of the common market, effective protection of consumers’ rights and respect for the legislative autonomy of Member States.
Keywords: Unia Europejska; prawo prywatne; prawo umów; działania legislacyjne